Cdk5 Inhibitory Peptide Prevents Loss of Dopaminergic Neurons and Alleviates Behavioral Changes in an MPTP Induced Parkinson’s Disease Mouse Model - He, Rongni; Huang, Wei; Huang, Yaowei; Xu, Miaojing; Song, Pingping; Huang, Yinwei; Xie, Huifang; Hu, Yafang (Frontiers in Aging Neuroscience, 2018)
Parkinson's disease (PD) is one of the most affected neurodegenerative diseases in the world. Deregulation of cyclin-dependent kinase 5 (Cdk5) is believed to play an important role in neurodegenerative diseases including PD. p25 is a cleavage peptide of p35, a physiologic activator of Cdk5. p25 combines to Cdk5 and leads to the hyperactivity of Cdk5, which in turn hyperphosphorylates downstream substrates and leads to neuroinflammation and apoptosis of neurons. Previously, we have demonstrated that adeno-associated virus serotype-9 (AAV9) mediated Cdk5 inhibitory peptide (CIP) inhibits the activity of Cdk5/p25 complex and alleviates pathologic and behavioral changes in Alzheimer's disease mouse model. In this study, we evaluated whether AAV9-CIP protected dopaminergic neurons in 1-methyl-4-phe-nyl-1,2,3,6-tetrahydropyridine-probenecid (MPTP/p) induced PD mouse model. The data showed that administration of AAV9-CIP by intracerebroventricular injection one week before MPTP/p exposure protected loss of dopaminergic neurons in substantia nigra compact of the model mice. Importantly, AAV9-CIP also alleviated the motor and anxiety-like symptoms of the disease animals. In summary, AAV9 mediated CIP might be a potential intervention for PD.